Optical adhesive material and preparation method of shell
By adding anti-blue light components to the optical glue material of the electronic device housing, the problem of photochromic materials degradation and yellowing when exposed to high blue light is solved, the durability and weather resistance of the equipment are improved, and the photochromicity is achieved. Effect.
Patent Information
- Application Number
- CN202411515808.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-03
AI Technical Summary
Existing photochromic materials are prone to photodegradation and yellowing under long-term exposure of light sources, resulting in a shortening of the service life of the article.
Using an optical glue material preparation method, including mixing components such as acrylic methyl methacrylate, methyl acrylate and azobisisobutyronitrile, adding photochromic toner and anti-blue light absorber after heating reaction to form anti-anti- Blu-ray optical glue material, and coated on the substrate diaphragm, bonded with the composite sheet to form an electronic device housing.
This method optimizes the problem of high blue light energy degradation and yellowing of glue materials in the 380-420nm band, improves the durability and weather resistance of the electronic equipment shell, and achieves the photochromic effect without affecting the existing process requirements.
Smart Images

Figure CN119242228A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of surface treatment of equipment housings, and specifically relates to a method for preparing an optical adhesive material and a housing. Background Art
[0002] Photochromic materials are widely used in various industries. Objects made of photochromic materials can change color significantly under the irradiation of external light sources, such as mobile phone housings, eyeglass lenses, etc. Photochromic materials in related technologies are usually prepared by adding photochromic color powder into a substrate to further form photochromic objects. Photochromic materials prepared in this way usually undergo photodegradation under long-term irradiation of light sources, causing the objects to turn yellow and age, shortening the service life of the items. Summary of the invention
[0003] The purpose of the embodiments of the present application is to provide a method for preparing an optical adhesive material and a housing, so as to solve the problem that the existing photochromic materials are prone to photodegradation and yellowing.
[0004] In order to solve the above technical problems, this application is implemented as follows:
[0005] In a first aspect, an embodiment of the present application provides a method for preparing an optical adhesive material, comprising:
[0006] Mixing monomers, initiators and solvents to form a mixture; wherein the monomers include methyl methacrylate and methyl acrylate; the initiator includes azobisisobutyronitrile;
[0007] Adding the initiator and the crosslinking agent to the mixture and heating the mixture for reaction to obtain an acrylate glue solution;
[0008] Add photochromic color powder and anti-blue light absorber into the acrylic ester adhesive solution, stir and mix, and obtain an optical adhesive material.
[0009] In a second aspect, an embodiment of the present application provides a method for preparing a shell, comprising:
[0010] Applying the optical adhesive material prepared by the above method on the first surface of the substrate film to obtain a coated film;
[0011] The coated film is laminated to the composite board.
[0012] In a third aspect, an embodiment of the present application provides an electronic device housing, which is manufactured using the above-mentioned housing preparation method.
[0013] The optical adhesive material formula provided in the embodiments of the present application optimizes the degradation and yellowing problems of the adhesive material when irradiated with high blue light energy in the 380-420nm band. The optical adhesive material has an anti-blue light effect and can be used to prepare the shell of electronic equipment. It can enable the shell of the electronic equipment to achieve a photochromic effect and be anti-blue light, making the prepared electronic equipment shell more durable and weather-resistant. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 is a schematic flow chart of a method for preparing an optical adhesive material according to an embodiment of the present application;
[0015] Figure 2 is a schematic structural diagram of a coated membrane according to an embodiment of the present application;
[0016] Figure 3 is a schematic diagram of laminating a coated film sheet and a composite sheet using a roll-to-sheet laminating process in an embodiment of the present application;
[0017] Figure 4 It is a schematic diagram of an electronic device housing according to an embodiment of the present application. DETAILED DESCRIPTION
[0018] The following will be combined with the drawings in the embodiments of the present application to clearly describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments in the present application belong to the scope of protection of this application.
[0019] The terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable under appropriate circumstances, so that the embodiments of the present application can be implemented in an order other than those illustrated or described here, and the objects distinguished by "first", "second", etc. are generally of one type, and the number of objects is not limited. For example, the first object can be one or more. In addition, "and / or" in the specification and claims represents at least one of the connected objects, and the character " / " generally indicates that the objects associated with each other are in an "or" relationship.
[0020] The optical adhesive material, the preparation method of the electronic device housing and the electronic device housing provided in the embodiments of the present application are described in detail below with reference to the accompanying drawings through specific embodiments and their application scenarios.
[0021] like Figure 1 As shown, the embodiment of the present application provides a method for preparing an optical adhesive material, comprising:
[0022] Step 101, mixing monomers, initiators and solvents to form a mixture; wherein the monomers include propylene methyl methacrylate and methyl acrylate; the initiator includes azobisisobutyronitrile;
[0023] Step 102, adding the initiator and the cross-linking agent to the mixture, and heating the mixture for reaction to obtain an acrylate glue solution;
[0024] Step 103: Add photochromic color powder and anti-blue light absorber to the acrylic ester adhesive solution, stir and mix, and obtain an optical adhesive material.
[0025] In this embodiment, the optical adhesive material may be an optically clear adhesive (OCA) adhesive material. When preparing the optical adhesive material, firstly, monomers, initiators and solvents are added to form a mixture. Specifically, the monomers include methyl methacrylate and methyl acrylate; the initiator is azobisisobutyronitrile; and the solvent is ethyl acetate.
[0026] Optionally, in the mixture formed by mixing the monomer, the initiator and the solvent, the mass ratio of the propylene methyl methacrylate, the methyl acrylate and the initiator is 80:14:5. The mass of the propylene methyl methacrylate is 75%-85% of the mass of the mixture; the mass of the methyl acrylate is 12%-15% of the mass of the mixture; the mass of the initiator is 3%-7% of the mass of the mixture. The mass ratio of the propylene methyl methacrylate, the methyl acrylate, the initiator and the solvent is 80:14:5:1.
[0027] Optionally, the step of mixing the monomer, the initiator and the solvent to form a mixture includes: mixing and stirring the monomer, the initiator and the solvent in an inert environment and heating the mixture to 60-65° C. to form a mixture.
[0028] In this embodiment, methyl methacrylate, methyl acrylate, azobisisobutyronitrile, and ethyl acetate are poured into a reaction kettle in a ratio of 80:14:5:1, and the agitator is started to stir at a medium speed. The stirring rate can be: 3000±100r / min, and the stirring time can be: 5-10min. Nitrogen is introduced and the temperature is raised to 60-65 degrees to form a mixture.
[0029] Optionally, an initiator and a cross-linking agent are added to the mixture, and the temperature is raised for reaction to obtain an acrylic ester glue solution, comprising:
[0030] The reaction temperature of the mixture is raised to 70-75° C., and the initiator is added dropwise to the mixture for reaction, and the adding time is 55 to 65 minutes; for example, the adding time may be 1 hour;
[0031] The reaction temperature is raised to 75-80°C, and the initiator and the crosslinking agent are continuously added and the reaction is continued for 115 to 125 minutes to obtain an acrylate adhesive solution. For example, the initiator and the crosslinking agent can be added and the reaction is continued for 2 hours.
[0032] In this embodiment, after obtaining the mixture, the reaction temperature of the mixture is raised to 70-75 degrees, and the mixture is continuously added dropwise for 55 minutes to 65 minutes (e.g., 1 hour), and 0.5% initiator azobisisobutyronitrile is continuously added to continue the reaction; the temperature is raised to 75-80 degrees, 0.5% initiator and 5% cross-linking agent divinylbenzene are added, and stirring is continued for 115 minutes to 125 minutes (e.g., 2 hours) to allow the monomer to fully react and ensure that the initiator and the cross-linking agent are evenly distributed to obtain an acrylic glue solution.
[0033] Add photochromic color powder and anti-blue light absorber into the acrylic ester adhesive solution, stir and mix, and obtain an optical adhesive material.
[0034] Optionally, at least one of nanoparticles, plasticizers, antioxidants, and ultraviolet absorbers is further added to the acrylic glue. Optionally, hydroxyanisole and isocyanoethyl methacrylate are further added to the acrylic glue; wherein the mass of the hydroxyanisole is 0.1%-0.15% of the mass of the acrylic glue; and the mass of the isocyanoethyl methacrylate is 3%-5% of the mass of the acrylic glue.
[0035] Optionally, the mass of the photochromic toner is 1.8%-2% of the mass of the acrylic glue; and / or
[0036] The mass of the anti-blue light absorber is 0.3%-0.5% of the mass of the acrylic glue; and / or
[0037] The mass of the nanoparticles is 0.5%-1% of the mass of the acrylic ester glue; and / or
[0038] The mass of the plasticizer is 2%-3% of the mass of the acrylic ester glue; and / or
[0039] The mass of the antioxidant is 0.2%-0.5% of the mass of the acrylic ester glue; and / or
[0040] The mass of the ultraviolet absorber is 0.5%-0.8% of the mass of the acrylic ester glue.
[0041] In this embodiment, after obtaining the acrylic glue, photochromic color powder is added, and the amount of the photochromic color powder added can be: 1.8%-2%; anti-blue light absorber is added, and the amount of the anti-blue light absorber added can be: 0.3%-0.5%, and the anti-blue light absorber includes: cyanine structure-modified compounds, phenol derivatives, benzophenone triazine and benzotriazole. Optionally, nanoparticles can also be added: such as nano zinc oxide, which is used to enhance optical stability and anti-blue light performance. The proportion of nanoparticles needs to be controlled at: 0.5%-1%, ensuring a certain degree of blue light resistance while avoiding excessive effects on the excitation of the photochromic color powder. Optionally, plasticizers can also be added: such as dioctyl phthalate, which is used to improve flexibility, and the proportion of plasticizers is: 2-3%. Optionally, antioxidants and ultraviolet absorbers can be added to improve light stability, with a ratio of 0.5-1%. For example, the amount of antioxidant added can be 0.2%-0.5% and the amount of ultraviolet absorber added can be 0.5%-0.8%. Optionally, ethyl acetate can be added to adjust the viscosity of the acrylic glue, and hydroxyanisole and isocyanoethyl methacrylate can be added to ensure the grafting efficiency of the glue. The reaction temperature is 50-55 degrees, and the stirring is continued at a medium speed. The stirring time can be 6-8 hours to ensure that all kinds of additives are evenly mixed and dispersed. After sufficient stirring, a photochromic and blue light-resistant optical adhesive material is obtained.
[0042] Optionally, it also includes: degassing the optical adhesive material. Pour the mixed optical adhesive material into a vacuum degassing machine, the degassing temperature can be: 50-60 degrees; the degassing pressure is: 5-6kg; the degassing time is: 30-40min, to ensure that the bubbles are completely removed. During the degassing process, check the glue liquid state regularly every 4 hours to ensure that the bubbles are completely removed and the glue liquid is uniform and free of bubbles.
[0043] The optical adhesive material formula provided in the embodiments of the present application optimizes the degradation and yellowing problems of the adhesive material when irradiated with high blue light energy in the 380-420nm band. The optical adhesive material has an anti-blue light effect and can be used to prepare the shell of electronic equipment. It can enable the shell of the electronic equipment to achieve a photochromic effect and be anti-blue light, making the prepared electronic equipment shell more durable and weather-resistant.
[0044] An embodiment of the present application also provides a method for preparing a housing, comprising:
[0045] The optical adhesive material prepared by the above optical adhesive material preparation method is coated on the first surface of the substrate film to obtain a coated film; and the coated film is bonded to the composite plate.
[0046] Optionally, the substrate film is a polycarbonate PC film. The PC film has stretchability, and when the coating film is attached to the composite board, the coating film can be stretched until its edge has a partial margin relative to the composite board, thereby avoiding tearing during subsequent baking treatment.
[0047] Optionally, coating the optical adhesive material on the first surface of the substrate film to obtain the coated film comprises:
[0048] The optical adhesive material is subjected to a degassing treatment; the degassing optical adhesive material is coated on the first surface of the substrate film, and the coated substrate film is dried and pre-cured; a release film is attached to the surface of the optical adhesive material to obtain a coated film.
[0049] Optionally, laminating the coated film to the composite sheet includes:
[0050] The coated film is bonded to the composite sheet through a roll-to-sheet process; wherein the coated film is a roll material and the composite sheet material is a whole sheet material.
[0051] Specifically, taking the optical adhesive material as OCA and the substrate film as PC film as an example, the process of coating the optical adhesive material on the first surface of the substrate film to obtain the coated film may include:
[0052] 11) Preparation of optical adhesive materials: Pour the OCA glue into a blender and stir at a low speed for 13-15 minutes. The stirring rate is 600-800r / min. After stirring, pour the OCA glue into a vacuum degassing machine for degassing. The degassing temperature is 50-60 degrees; the degassing pressure is 5-6kg; the degassing time is 25-30 minutes. Ensure that the bubbles are completely discharged.
[0053] 12) Apply OCA glue to PC film: The thickness of the OCA glue layer applied on the composite board electronic device housing is set at 23-27um. During the coating process, the OCA glue is squeezed out from the gap between the upper and lower molds, forming liquid beads between the moving PC substrate and transferred to the surface of the PC substrate to form a wet film. The degassed OCA glue is transported to the slit die through the liquid supply system. The OCA glue is evenly coated on the surface of the PC diaphragm through the opening of the slit die. The liquid supply is controlled by adjusting the flow rate of the pump. The liquid supply determines the amount of OCA glue passing through the slit die per unit time, which directly affects the coating thickness. The flow rate of the liquid supply system is set to 185-187ml / min to ensure stable liquid supply and film thickness. The opening width of the slit die is adjusted to 500mm to adapt to the size of the PC diaphragm. The opening gap of the slit die is set to 200-300um to ensure uniform glue. The PC diaphragm is installed in the first unwinding shaft of the substrate conveying system, and the substrate conveying system is started. The PC diaphragm passes under the slit die at a constant speed. The substrate movement speed is set to 15-18m / min to match the liquid supply rate to ensure uniform coating and achieve coating film thickness.
[0054] 13) Post-processing lamination: After coating, the PC film enters the baking line for drying and pre-curing. The baking temperature is: 65-70 degrees; the baking time is: 2-4 minutes; after drying, it goes to the laminating system for laminating with the OCA release film on the second unwinding shaft. The release film is selected to be 100-125um thick. The release film is in contact with the surface of the OCA adhesive layer. Appropriate pressure is applied through the laminating roller. The laminating roller pressure can be set to 0.5Mpa to ensure that the release film is evenly adhered to the surface of the OCA glue. At the same time, the reel works synchronously, and the overall unwinding and rewinding speed of the substrate movement speed remains consistent at 15-18m / min. Ensure that the release film is evenly covered on the surface of the OCA glue without bubbles and wrinkles, and store the laminated PC film in a dust-free environment to avoid dust and impurity pollution.
[0055] The structure of the coated membrane is as follows Figure 2 As shown, it includes: a substrate film 21; an optical adhesive material layer 22 coated on the first surface of the substrate film 21; a release film 23 attached to the optical adhesive material layer 22; and a protective film 24 attached to the second surface of the substrate film 21. The thickness of the substrate film 21 can be 0.125 mm; the thickness of the optical adhesive material layer 22 can be 25 um; the thickness of the release film 23 can be 125 um; and the thickness of the protective film 24 can be 30 um.
[0056] Specifically, the process of laminating the coated film to the composite sheet may include:
[0057] 21) Roll-to-sheet lamination: The coated film is a roll material, and the composite sheet is a whole sheet material. The schematic diagram of the roll-to-sheet lamination of this application is as follows Figure 3The roll-to-sheet lamination is different from the conventional single terminal shell lamination of PET film. In the roll-to-sheet lamination, multiple shells 321 are laminated on the same composite sheet 32 at the same time, which has the advantages of high efficiency, low cost and good consistency.
[0058] like Figure 3 As shown, the composite sheet is placed on the working platform 31 of the large-plate vacuum laminating machine, the composite sheet 32 is fixed by a jig, and the surface of the composite sheet 32 is dusted by a plasma spray gun to ensure surface cleanliness; the release film on the back of the composite sheet and the coated film 33 is removed, and the coated film 33 is aligned with the composite sheet 32 by a customized jig 34. According to the stretchability of the coated film 33, the single-side margin of the edge of the film is controlled to be 1-1.2mm to avoid excessive stretching and cracking during post-process baking. Lay the optical adhesive material 331 on the coated film 33 onto the composite plate, and use a laminating jig to gently press the coated film 33 and the composite plate 32 to ensure initial adhesion and avoid uneven adhesive layer; start the vacuum laminating machine, extract the air in the vacuum chamber to form a negative pressure environment with a vacuum degree of -100KPa. A reasonable vacuum degree ensures that the applied pressure is evenly distributed to avoid incomplete bonding and material deformation. Simultaneously, use a jig to apply laminating pressure with a pressure of 5Mpa and a laminating time of 5s to ensure that the coated film 33 and the composite plate 32 are completely bonded.
[0059] 22) Degassing process: Degassing is performed on the composite sheet after laminating the coated film to further remove the tiny bubbles remaining in the laminating process; the laminated composite sheet is placed in the degassing machine, and the pressure in the equipment is gradually increased. The degassing pressure is 15.0kgf, and the temperature is gradually increased. The degassing temperature is 60-70 degrees. The set temperature and pressure are maintained. The degassing time is 30-40 minutes. After the degassing is completed, the pressure is gradually reduced to prevent sudden decompression from causing deformation or damage to the material, and the material is naturally cooled to return to room temperature.
[0060] This embodiment can solve the problems of warping, wrinkling, bubbles, uneven adhesive layer, etc. in the process of roll-to-roll photochromic coating film bonding of composite panels, and can avoid the problem of coating film delamination in the post-process.
[0061] Optionally, after the coated film is bonded to the composite board, UV transfer process, optical film coating, metal film system, offset printing, silk screen printing process, etc. can be superimposed on the bonded coated film to meet the appearance effect requirements of the electronic equipment casing.
[0062] For example, after the coated film is laminated to the composite sheet, a UV transfer process is performed on the coated film, including:
[0063] Place the composite sheet with the coated film on the working platform of the transfer machine, start the transfer machine, place the texture mold on the transfer platform and fix it with a fixture, start the machine, and use the dispensing nozzle to dispense UV glue on the mold. The dispensing pressure is set to: 0.2-03Mpa; the glue flow rate is set to 70-80%; the dispensing amount is set to 5-6g to ensure that the UV glue can be evenly attached to the texture mold. Remove the protective film on the coated film, with the composite sheet facing up and the coated film facing down, and use the fixture to cover the surface of the coated film on the mold with the UV glue liquid; after covering, start the roller to roll and fill the UV glue liquid between the coated film and the mold. In order to ensure that the UV glue can be fully filled and the coated film will not be scratched or deformed by roller pressure, the roller hardness is set to 85-90, the roller pressure is set to 0.5-0.6Mpa, the roller maintenance time is once every 1 hour, and the roller movement rate is set to 20% to ensure that the UV glue film thickness on the coated film meets 10-15um. After the transfer is completed on the coated film, light curing is immediately carried out. The curing form can be cured by dual LED lamps. The curing time is 10s, and the LED light intensity is controlled to 600-700mw / cm2 to avoid excessive light intensity, which will cause the board and the coated film to warp and deform. After the UV glue on the coated film is cured, the composite board is demolded from the mold and secondary curing is carried out. The second curing uses a mercury lamp with an energy setting of 1200mj / cm2 to ensure that the UV glue on the coated film is completely cured.
[0064] For another example, after the coated film is bonded to the composite sheet, a film is plated on the coated film, including:
[0065] The composite sheet after the texture is transferred on the coated film is subjected to vacuum evaporation coating process to meet the appearance requirements of the electronic equipment shell. During the coating process, the composite sheet attached to the coated film has an increased degassing volume, the vacuum background value is controlled below 0.003Pa, and the process vacuum value is controlled at about 0.02Pa; and an ion source is required for cleaning, the voltage is controlled to 120-140V, the current is 6-8A, the argon flow rate is controlled to 60-70sccm, and the ion source cleaning time is 600s to improve the adhesion of the coating target on the coated film. The temperature of the coating chamber is controlled at 70-80 degrees, so that the coated film substrate can be better exhausted while avoiding the warping and deformation of the composite sheet attached to the coated film; the main film materials for electroplating on the coated film are silicon dioxide, titanium pentoxide and metal indium, which can ensure the appearance effect while meeting the production requirements of the composite sheet attached to the coated film as the shell of the electronic equipment.
[0066] Another example: after the coated film is bonded to the composite board, screen printing ink on the coated film includes:
[0067] 1) Silk screen ink
[0068] Use the screen printing jig to fix the composite sheet with the coated film on the screen printing machine table, with the coated film facing up, adjust the screen to the appropriate position, and pour the ink into the ink tank of the screen printing machine; use a scraper to evenly press the screen, and scrape the ink through the hollow part of the screen to the surface of the sheet. Screen material: nylon; nylon has good elasticity and flexibility, and can be well applied to the surface of the coated film during the printing process. Nylon has good tolerance to solvents and additives in the ink and is not easily corroded during mass production. Screen tension: 22N, mesh spacing: 1.2~2.0mm, screen mesh number: 200~350 mesh, film thickness printed on the coated film: greater than 4um, to ensure weather resistance and uniformity. Scraper material: polyurethane. Polyurethane scrapers have excellent wear resistance and are suitable for long-term high-frequency use in mass production environments. They have good elasticity and flexibility and can provide uniform pressure on the surface of the coated film without scratching or bruising. They also have good tolerance to ink and solvents and are not easily corroded. Scraper hardness: 75-85 Shore hardness to ensure printing accuracy and service life; Scraper angle: 45 degrees to ensure that the scraper edge can evenly scrape the ink; Repeated printing times: 2-4 times to ensure the uniformity of the ink, and the total film thickness of the ink: 40um-60um to ensure the stability of the color change of the coated film.
[0069] 2) Baking and curing ink
[0070] After printing ink on the coated film, the composite board needs to be dried in an oven at a baking temperature of 90 degrees to 100 degrees for 60 minutes to avoid excessively high temperatures during the heating process, which may cause the optical adhesive material to fail or the ink to not be completely cured, resulting in abnormal adhesion between the ink and the coated film, and ink shedding and ink bubbling during high temperature and high humidity environmental tests.
[0071] In the embodiment of the present application, the photochromic appearance effect of the composite plate is achieved by laminating a photochromic coating film on the composite plate, and the optical adhesive material formula of the coating film optimizes the degradation and yellowing of the adhesive material under the irradiation of high blue light energy in the 380-420nm band, so that the prepared electronic device housing has a photochromic effect and is resistant to blue light, and is more durable and weather-resistant. The electronic device housing prepared using this method will not affect the existing process requirements. For example, a UV transfer process can be superimposed on the coating film, and optical film, metal film system, offset printing, and silk screen printing processes can be plated to meet the existing battery cover appearance effect requirements. And the film will not fall off in tests such as high temperature, high humidity, and ultraviolet rays.
[0072] The embodiment of the present application also provides an electronic device housing, which is prepared using the above-mentioned housing preparation method.
[0073] Optionally, the electronic device housing further includes:
[0074] UV glue layer;
[0075] Coating layer;
[0076] Ink layer.
[0077] In this embodiment, the electronic device housing is as follows Figure 4 As shown, including:
[0078] A coating film 41, the coating film 41 is composed of a base film 411 and an optical adhesive material layer 412 coated on a first surface of the base film 411;
[0079] The composite sheet 42 is bonded to the coating film 41;
[0080] The UV glue layer 43 , the coating layer 44 , and the ink layer 45 are attached to the second surface of the substrate film 411 .
[0081] The embodiments of the present application achieve the photochromic appearance effect of the composite board by laminating a photochromic coating film on the composite board, and at the same time, can superimpose a UV transfer process on the coating film, coat an optical film, a metal film system, and offset printing, and a silk screen printing process to meet the existing battery cover appearance effect requirements.
[0082] Compared with the traditional photochromic PET film lamination process, the roll-to-roll lamination process is used to laminate the photochromic coated film onto the composite board, which can not only improve problems such as warping and deformation, but also significantly reduce the production efficiency and cost of the equipment shell of the composite board during the production process.
[0083] The composite sheet electronic equipment housing with photochromic effect is mainly achieved by adding photochromic color powder to the optical adhesive material layer in the coating film. The innovative modified optical adhesive liquid formula is optimized to prevent the degradation and yellowing of optical adhesive under high blue light energy in the 380-420nm band. An innovative anti-blue light optical adhesive liquid system is developed to make the color change of the sheet more durable and weather-resistant.
[0084] The embodiment of the present application also provides an electronic device, including the above-mentioned electronic device housing. The electronic device may be a terminal, or may be other devices other than a terminal. Exemplarily, the electronic device may be a mobile phone, a tablet computer, a laptop computer, a PDA, a vehicle-mounted electronic device, a mobile Internet device (Mobile Internet Device, MID), an augmented reality (augmented reality, AR) / virtual reality (virtual reality, VR) device, a robot, a wearable device, an ultra-mobile personal computer (ultra-mobile personal computer, UMPC), a netbook or a personal digital assistant (personal digital assistant, PDA), etc. It may also be a server, a network attached storage (Network Attached Storage, NAS), a personal computer (personal computer, PC), a television (television, TV), a teller machine or a self-service machine, etc., which is not specifically limited in the embodiment of the present application.
[0085] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0086] Through the description of the above implementation methods, those skilled in the art can clearly understand that the above-mentioned embodiment methods can be implemented by means of software plus a necessary general hardware platform, and of course by hardware, but in many cases the former is a better implementation method. Based on such an understanding, the technical solution of the present application, or the part that contributes to the prior art, can be embodied in the form of a computer software product, which is stored in a storage medium (such as ROM / RAM, a disk, or an optical disk), and includes a number of instructions for a terminal (which can be a mobile phone, a computer, a server, or a network device, etc.) to execute the methods described in each embodiment of the present application.
Claims
1. A method for preparing an optical adhesive material, characterized in that: include: Mixing monomers, initiators and solvents to form a mixture; wherein the monomers include methyl methacrylate and methyl acrylate; the initiator includes azobisisobutyronitrile; Adding the initiator and the crosslinking agent to the mixture and heating the mixture for reaction to obtain an acrylate glue solution; Add photochromic color powder and anti-blue light absorber into the acrylic ester adhesive solution, stir and mix, and obtain an optical adhesive material.
2. The preparation method according to claim 1, characterized in that: At least one of nanoparticles, plasticizers, antioxidants and ultraviolet absorbers is also added to the acrylic adhesive.
3. The preparation method according to claim 2, characterized in that: The mass of the photochromic toner is 1.8%-2% of the mass of the acrylic ester glue; and / or The mass of the anti-blue light absorber is 0.3%-0.5% of the mass of the acrylic glue; and / or The mass of the nanoparticles is 0.5%-1% of the mass of the acrylic ester glue; and / or The mass of the plasticizer is 2%-3% of the mass of the acrylic ester glue; and / or The mass of the antioxidant is 0.2%-0.5% of the mass of the acrylic ester glue; and / or The mass of the ultraviolet absorber is 0.5%-0.8% of the mass of the acrylic ester glue.
4. The preparation method according to claim 1, characterized in that: In the mixture, the mass ratio of the methyl methacrylate, the methyl acrylate and the initiator is 80:14:5; The mass of the methyl methacrylate is 75%-85% of the mass of the mixture; the mass of the methyl acrylate is 12%-15% of the mass of the mixture; and the mass of the initiator is 3%-7% of the mass of the mixture.
5. The preparation method according to claim 1, characterized in that: Adding hydroxyanisole and isocyanoethyl methacrylate to the acrylic ester glue; The mass of the hydroxyanisole is 0.1%-0.15% of the mass of the acrylic ester glue; the mass of the isocyanoethyl methacrylate is 3%-5% of the mass of the acrylic ester glue.
6. The preparation method according to claim 1, characterized in that: The step of mixing the monomer, the initiator and the solvent to form a mixture comprises: The monomer, the initiator and the solvent are mixed and stirred in an inert environment and heated to 60-65° C. to form a mixture.
7. The preparation method according to claim 6, characterized in that: Adding an initiator and a crosslinking agent to the mixture and heating the mixture for reaction to obtain an acrylic ester glue solution, comprising: The reaction temperature of the mixture is raised to 70-75° C., and the initiator is added dropwise to the mixture for reaction, and the adding time is 55 to 65 minutes; The reaction temperature is raised to 75-80° C., the initiator and the cross-linking agent are continuously added dropwise and the reaction is continued for 115 to 125 minutes to obtain the acrylic ester glue solution.
8. A method for preparing a shell, characterized in that: include: Coating the optical adhesive material prepared by the method of any one of claims 1 to 7 on the first surface of the substrate film to obtain a coated film; The coated film is laminated to the composite board.
9. The method according to claim 8, characterized in that The optical adhesive material is coated on the first surface of the substrate film to obtain the coated film, comprising: Degassing the optical adhesive material; Applying the degassing treated optical adhesive material on the first surface of the substrate film, and drying and pre-curing the applied substrate film; A release film is attached to the surface of the optical adhesive material to obtain the coated film sheet after lamination.
10. The method according to claim 8, characterized in that The substrate film is a polycarbonate PC film.
Citation Information
Cited By
Photochromic polyacrylate material, photochromic adhesive sheet and preparation method thereof
CN121554633A
